The correlation between immunoexpression of estrogen receptor and the severity of periodontal disease - Yuliana Mahdiyah Da’at Arina; S. Sunardhi Widyaputra; Koeswadji Koeswadji (Dental Journal (Majalah Kedokteran Gigi), 2010)
Background: The decreased level of estrogen during menopause may be one of the risk factors of periodontal disease. The influence of estrogen to periodontal tissue disturbance is mediated by the presence of estrogen receptor on tissue. The precise mechanism how the estrogens mediate this effect is still unclear. Purpose: The aim of this study was to determine the correlation between estrogen receptor α and ß on the periodontal pocket of women who had severe chronic periodontitis measured based on the periodontal pocket depth. Methods: Twenty four periodontitis patients from menopausal and productive women according to the criteria were examined upon her periodontal status and immunoexpression of estrogen receptor α and ß on their periodontal pocket wall. Results: The result showed that in the menopausal and productive women, immunoexpression of estrogen receptor α and ß was not correlated with the periodontal pocket depth (p>0.05). However, the pocket depth seemed to show higher correlation with immunoexpression of estrogen receptor α than that with estrogen receptor ß, r=0.37 vs. r=0.12 for menopausal women, and r=41 vs. r=0.11 for productive women. Conclusion: It was concluded that no significant correlation was found between the estrogen receptor and periodontal pocket depth both on menopausal and productive women, presumed that estrogen has little role in the severity of periodontitis based on periodontal pocket depth. However, the estrogen receptor α has valuable effect on the severity of periodontal disease more than the estrogen receptor ß.Latar belakang: Berkurangnya kadar estrogen pada masa menopause merupakan salah satu faktor resiko penyakit periodontal. Peran estrogen dalam kerusakan jaringan periodontal dimediatori oleh reseptor estrogen α dan ß yang terdapat dalam jaringan. Akan tetapi, mekanisme estrogen mempengaruhi efek ini sampai saat ini masih belum jelas. Tujuan: Penelitian ini bertujuan untuk menentukan korelasi antara reseptor estrogen pada poket periodontal wanita menopause penderita periodontitis kronis dengan keparahan periodontitis yang ditentukan berdasarkan kedalaman poket. Metode: Dilakukan pemeriksaan status periodontal dan immunoekspresi reseptor estrogen α dan ß pada dinding poket periodontal dari 24 wanita menopause dan belum menopause penderita periodontitis yang sesuai dengan kriteria yang telah ditetapkan. Hasil: Hasil mendapatkan bahwa immunoekspresi reseptor estrogen α dan ß tidak berkorelasi dengan kedalaman poket periodontal wanita menopause dan belum menopause (p>0,05). Meskipun demikian, kedalaman poket periodontal tampak lebih berkorelasi dengan reseptor estrogen α daripada dengan reseptor estrogen ß, dengan nilai r=0,37 vs r=0,12 pada wanita menopause, dan r=0,41 vs r=0,11 pada wanita belum menopause. Kesimpulan: Dapat disimpulkan bahwa tidak terdapat korelasi yang signifikan antara reseptor estrogen dan kedalaman poket periodontal wanita menopause dan belum menopause sehingga diduga bahwa estrogen mempunyai sedikit pengaruh pada keparahan periodontitis. Meskipun demikian, reseptor estrogen α tampak lebih berperan terhadap keparahan penyakit periodontal dibandingkan reseptor estrogen ß.